Diurnal Critical Latitude and the Latitude Dependence of Internal Tides, Internal Waves, and Mixing Based on Barcoo Seamount. Issue 10 (16th October 2017) - Robertson, Robin; Dong, Jihai; Hartlipp, Paul
Abstract: Vertical mixing is a key issue in ocean circulation modeling today. Mixing, particularly tidal mixing, is poorly represented in ocean and climate models, which generally ignore critical latitude effects. Critical latitude is the latitude where the inertial frequency equals the tidal frequency and differs for each tidal constituent. Critical latitudes strongly influence generation and propagation of internal tides. Using a model, latitude effects on tidal interactions with a seamount were examined by varying the latitude from 20° to 38°, through the range of the diurnal critical latitudes. The diurnal critical latitudes were found to strongly influence propagation of the diurnal internal tides, the magnitude of the semidiurnal tides, the energy in the harmonic and higher frequencies, the barotropic mean flow, and the diffusivities. The strongest effects occurred between the K1 and O1 critical latitudes. Here the semidiurnal tides, harmonics, and high frequencies were enhanced, barotropic mean velocities weakened, energy at the harmonics and higher frequencies increased, and diffusivities increased. Spectral techniques indicate that most of these impacts are the result of nonlinear wave‐wave interactions and resonant phenomena with the prominent mechanism harmonic transfers. There was no evidence of parametric subharmonic instabilities. The semidiurnal tides indicated a resonant response at 20°S, which is near the latitude for the combined M2 and K1 tidal period, ∼19°S. Plain Language Summary: This study investigates how the ocean response to the tides changes with latitude using a series of model simulations for a seamount. It focuses on the latitudes which resonate with the daily tides, the diurnal critical latitudes, where small changes are amplified. The effects on mixing and the transfer of energy to other frequencies is a key aspect. It was found that even small tides significantly increase mixing near the K1 critical latitude . The transfer of energy increases near the diurnal critical latitudes. Energy transfers in currents from the daily tide to the twice daily tide were primarily around the seamount, whereas those from twice daily tides to their harmonics and high frequencies were around the seamount towards and away from to the seamount. Key Points: With horizontally uniform stratification, semidiurnal tidal activity peaked in the diurnal critical latitude range Diffusivities peaked at the K1 critical latitude, as determined in the model using the Nakanishi‐Niino vertical mixing parameterization Energy transfers were direction dependent, with more transfers occurring in the across‐slope direction at lower frequencies, particularly the semidiurnal tides